ACCOUNTABILITY OF ISLAMIC BASED NON-PROFIT SECTOR: THE CASE OF WAQF ORGANIZATIONS - Rochania Ayu Yunanda (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2016)
Waqf organizations have significant roles in a country to mobilize and distribute public funds. The uniqueness of waqf is that waqf assets should be in existence in perpetuity, therefore the assets must be well managed. Managing public assets must be based on transparency and accountability. The financial reports are prepared to meet the accountability and transparency purposes. Since there was no specifically standardized accounting measurement and report, waqf organisations often adopt the financial reporting practices of for-profit accounting standards to present their financial performance which are not wholly appropriate for non-profit. However, organisations managing waqf assets must also ensure that they follow the unique Islamic principles of waqf such as perpetual existence. Ensuring its accountability through financial reports could be useful to assess waqf‟s perpetual existence. This paper aims to examine the accountability of waqf organizations since accountability is needed to promote public trust in such organizations. Using content and financial statement analysis, this study examines the latest two years (2013-2014) annual reports of five different waqf organizations.Keywords: waqf, financial statement, accountability, reporting